Leaf Morphometric and Chlorophyll Content Study of Bisbul (Diospyros discolor Willd.) at the Bogor Botanical Garden - Irvan Fadli Wanda; Arief Noor Rachmadiyanto; Ade Ayu Oksari (Journal of Tropical Biodiversity and Biotechnology, 2022)
Bisbul (Diospyros discolor Willd.) is one of the collections from the Bogor Botanical (BBG). The wide distribution of this plant in Southeast Asia's tropical forests creates many morphometric variations of this species. The diversity of leaf morphometric variations of a plant species can be the basis for grouping various species. This study aimed to determine the morphometric diversity of Bisbul leaves from various locations of origin. The study took samples of bisbul leaves from Bogor Botanical Gardens from three accessions, namely the Philippines, West Java, and Papua. All the trees are over 30 years old. The leaves are taken based on a horizontal position, vertical crown, and leafage. The results showed that the origin of the location gave different multiplier values to calculate the area, namely the Philippines y = 0.733x + 0.034; West Java y = 0.765x-2,949; and Papua y = 0.758x-1.389. The length to leaf width ratio also has differences, namely, the Philippines, which is 2.64, West Java 2.65, and Papua 2.81. The chlorophyll content in young leaves increases in old leaves. The samples from Papua also have the highest chlorophyll content compared to the Philippines and West Java. This difference indicates morphometric variations between the three, even within one species. Some environmental conditions may affect shade areas and tree age. In addition, DNA research from accession D. discolor is also needed to determine the cause of the morphometric variation.